USABILITY EVALUATION OF PLAVON DUKCAPIL SIDOARJO WEBSITE USING WEBUSE METHODS: EVALUASI USABILITY WEBSITE PLAVON DUKCAPIL SIDOARJO MENGGUNAKAN METODE WEBUSE - Damayanti, Nadiah Della; Suyatno, Dwi Fatrianto (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2023)
Plavon Dukcapil is an online service website for population administration and civil registration developed by Disdukcapil Sidoarjo. There are 10 types of residence documents that can be taken care of through this website. The existence of this website is expected to facilitate the community in managing population documents independently. As time goes by, development will continue to be carried out. One important aspect that needs to be considered is the ease of use or usability factor. Therefore, there is a need for a usability evaluation to determine the level of website usability so that it can help Plavon Dukcapil develop according to user needs. The purpose of this study is to identify website usability problems and find out the results of the evaluation. Webuse is a method used to evaluate the usability of the Dukcapil Platform website with the help of a questionnaire that will be filled out by general respondents of website users. The Webuse method consists of 4 variables, namely content, organization and readability, navigation and links, user interface design and performance and effectiveness. Based on the evaluation results using the webuse method, it shows that 2 variables get a "Good" usability level, namely navigation and links and user interface design. While the other 2 variables namely content, organization and readability and performance and effectiveness get a usability level of "Moderate". In addition, 16 improvement recommendations were also produced as input for the development of the Dukcapil Plavon website in a better direction.